2019
DOI: 10.1186/s12978-019-0799-1
|View full text |Cite
|
Sign up to set email alerts
|

Stigma related to contraceptive use and abortion in Kenya: scale development and validation

Abstract: Background Stigma related to abortion and contraceptive use is a serious public health threat for young people, and validated scales to measure this stigma are scarce. The purposes of the study were to validate a newly constructed scale to measure the stigma of contraceptive use and to adapt a scale to measure the stigma of abortion. Methods A study nested in a cluster-randomised trial. In 2017, data was collected from 633 secondary school youths, in a semi-urban settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Three dimensions of abortion stigma are covered as subscales in the SABA scale: 1) negative stereotypes (8 items), 2) discrimination and exclusion (7 items) and 3) fear of contagion (3 items). Based on previous research within this project, the SABA scale was modified to address the perspective of adolescent girls [26]. This was done by replacing the word woman with girl in all items of the original scale.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three dimensions of abortion stigma are covered as subscales in the SABA scale: 1) negative stereotypes (8 items), 2) discrimination and exclusion (7 items) and 3) fear of contagion (3 items). Based on previous research within this project, the SABA scale was modified to address the perspective of adolescent girls [26]. This was done by replacing the word woman with girl in all items of the original scale.…”
Section: Data Collectionmentioning
confidence: 99%
“…This was done by replacing the word woman with girl in all items of the original scale. Furthermore, two items were added: "A married woman is more deserving of an abortion than an unmarried woman" and "A girl who has had an abortion should be prohibited from going to school" [26]. The modified SABA scale used in this study included a total of 20 items.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantable long-acting hormonal contraceptives, such as intrauterine devices (IUDs) and subcutaneous implants, will last for years as birth control methods that offer effective long-term contraception without the need for consumer intervention [18,20,21,35]. They are safer, cost-effective and have lower failure rates because of their low reliance on user compliance for e cacy compared to short-acting contraceptives [20,[36][37][38]. Studies have found that LARC can contribute to reducing subsequent unintended conceptions and that women having an abortion may be highly motivated to secure contraception, particularly LARC [18,38]; also, policies considering for heavy subsidization and upfront cost have been advocated [39] to ease the nancial burden of the users.…”
Section: Introductionmentioning
confidence: 99%
“…Although access to safe abortions and effective contraceptives has increased worldwide, accessibility is still a great barrier in many Low-and Middle-Income Countries (LMIC), including Nigeria. Also, the social stigma surrounding unintended pregnancies and abortion plays a critical role in the social, medical and legal marginalization of contraceptive services and abortion care [37], it is then surprising, given the demographic and programmatic signi cance of induced abortion that the research literature contains few probing investigations of the juxtaposition of contraception and abortion in the minds of those exposed to pregnancy risk [28] thus this research tends to examine the perception of women on abortion and its in uence on Long-Acting Contraceptive (LARC) use among women of reproductive ages in selected Nigerian states employing a cross-sectional study approach…”
Section: Introductionmentioning
confidence: 99%